Effectiveness of a Proactive Primary Care Program on Preserving Daily Functioning of Older People: A Cluster Randomized Controlled Trial. Issue 9 (26th July 2016) - Bleijenberg, Nienke; Drubbel, Irene; Schuurmans, Marieke J.; Dam, Hester ten; Zuithoff, Nicolaas P.A.; Numans, Mattijs E.; de Wit, Niek J.
Abstract : Objectives: To determine the effectiveness of a proactive primary care program on the daily functioning of older people in primary care. Design: Single‐blind, three‐arm, cluster‐randomized controlled trial with 1‐year follow‐up. Setting: Primary care setting, 39 general practices in the Netherlands. Participants: Community‐dwelling people aged 60 and older (N = 3, 092). Interventions: A frailty screening intervention using routine electronic medical record data to identify older people at risk of adverse events followed by usual care from a general practitioner; after the screening intervention, a nurse‐led care program consisting of a comprehensive geriatric assessment, evidence‐based care planning, care coordination, and follow‐up; usual care. Measurements: Primary outcome was daily functioning measured using the Katz‐15 (6 activities of daily living (ADLs), 8 instrumental activities of daily living (IADLs), one mobility item (range 0–15)); higher scores indicate greater dependence. Secondary outcomes included quality of life, primary care consultations, hospital admissions, emergency department visits, nursing home admissions, and mortality. Results: The participants in both intervention arms had less decline in daily functioning than those in the usual care arm at 12 months (mean Katz‐15 score: screening arm, 1.87, 95% confidence interval (CI) = 1.77–1.97; screening and nurse‐led care arm, 1.88, 95% CI = 1.80–1.96; control group, 2.03, 95% CI = 1.92–2.13; P = .03). No differences in quality of life were observed. Conclusion: Participants in both intervention groups had less decline than those in the control group at 1‐year follow‐up. Despite the statistically significant effect, the clinical relevance is uncertain at this point because of the small differences. Greater customizing of the intervention combined with prolonged follow‐up may lead to more‐robust results.